A fossil peat deposit from the Late Triassic (Carnian) of Zimbabwe with preserved cuticle of Pteridospermopsida and Ginkgoales, and its geological setting - Barale, Georges; Bamford, Marion K.; Gomez, Bernard; Broderick, Timothy J.; Raath, Michael A.; Cadman, Ann (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2005)
Well-preserved cuticular material of Pteridospermopsida and Ginkgoales from the Late Triassic of Zimbabwe is described here for the first time. It is preserved within a brown peat-like lens in the Upper Karoo Angwa Sandstone Formation. The locality is on the Manyima River in the lower portion of the mid-Zambezi Valley of Zimbabwe. Using SEM and light microscopy to identify the taxa, the fragmentary cuticles are of Pteridospermopsida type and have been assigned to Lepidopteris sp. (Peltaspermales) and Dicroidium sp. A, B, (Corystospermales). Cuticles of the ginkgoalean leaf genus, Sphenobaiera, are also described. Well-preserved ovules were found in close association with the cuticles, but as the stomata are not visible they cannot be assigned to any genus. Based on their close similarity to the Dicroidium flora of the South African Upper Karoo, the plants are considered to be equivalent to the South African Molteno Formation in age (Carnian). The palynoflora supports this age bracket, as does fauna preserved nearby. The taphonomic process was one of transport, sorting and deposition in a fluvial system.